Respostas
respondido por:
0
x - 2 = 1/4 . x
x - 2 = x/4
4.(x-2) = x
4x-8 = x
4x-x = 8
3x = 8
x = 8/3
ou
x = 2,666666666666667
x - 2 = x/4
4.(x-2) = x
4x-8 = x
4x-x = 8
3x = 8
x = 8/3
ou
x = 2,666666666666667
respondido por:
0
Multiplica toda equação por 4 , para eliminar a fração x/4
x - 2 = x / 4 (4)
4x - 8 = x
4x - x = 8
3x = 8
x = 8 /3
Resposta: x = 8/3
-----------------------
ou
x - 2 = x /4
x - x /4 = 2
( 4x - x ) / 4 = 2
3x / 4 = 2
3x = 2 * 4
3x = 8
x = 8 / 3
Resposta: x = 8/3
x - 2 = x / 4 (4)
4x - 8 = x
4x - x = 8
3x = 8
x = 8 /3
Resposta: x = 8/3
-----------------------
ou
x - 2 = x /4
x - x /4 = 2
( 4x - x ) / 4 = 2
3x / 4 = 2
3x = 2 * 4
3x = 8
x = 8 / 3
Resposta: x = 8/3
caio0202:
editado !
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás